A ética do amor como dimensão do cuidado em Terapia Ocupacional - Gabarra, Leonardo Lima (Universidade Federal de São Carlos, 2026)
The present study investigated the ethics of love and its inseparability from occupational therapy care. Far removed from romantic or charitable meanings, love is understood as a feeling-action with political and transformative power, capable of confronting the violence and oppression that permeate subjects and populations historically marginalized. The research analyzed interviews with occupational therapists, interpreted through thematic analysis. Two themes emerged, demonstrating how loving practices strengthen relationships, promote objective and subjective transformations—both individual and collective—and sustain the struggle against violence present in the lives of individuals and communities. Although recognized as essential, love remains stigmatized and is often associated with fragility or seen as incompatible with technique and professionalism. The results indicate that it must be assumed as an ethical and political force, capable of fostering horizontal relationships, affirming diversity, and resisting oppressive logics. In Occupational Therapy, the ethics of love appears as a condition for humanized and transformative care, shifting professional practice away from rigid protocols toward actions committed to life, dignity, and social justice. To embrace it as an ethic transversal to the caring professions is to affirm its collective, community-based, and liberatory dimension. “Politics of love” thus become an inspiration for sustaining the well-being of all beings—human or non-human—and for recognizing care as a practice of freedom.
The ethics of love as a dimension of care in Occupational Therapy
La ética del amor como dimensión del cuidado en Terapia Ocupacional
Keywords: Compromisso ético-político; Prática profissional; Afeto; Sentimento-ação; Políticas do amor; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar; 4. Educação de Qualidade